Risk-Taking Propensity in Older Adolescents: Internalizing Symptoms, Gender, and Negative Reinforcement. Issue 3 (3rd July 2017) - Dahne, Jennifer; Lim, Aaron C.; Borges, Allison M.; MacPherson, Laura
Abstract : Objective : Engagement in risk behaviors, including substance use, risky sex, and violence, tends to increase throughout adolescence into young adulthood. One motivational process that may underlie risk behaviors during adolescence is negative reinforcement. Moreover, gender and internalizing symptoms (e.g., depression and anxiety) may both convey risk for negative reinforcement–based risk taking. Along these lines, the aims of the current study were to (a) examine gender differences in negative reinforcement–based risk-taking propensity and (b) examine internalizing symptoms as a moderator of the relationship between gender and negative reinforcement–based risk-taking propensity. Method : Participants included 103 youth between the ages of 18 and 21 (50.49% female, age M ( SD ) = 19.41(1.06)) who were recruited from a large Mid-Atlantic university between September 2013 and November 2014. Participants completed self-report assessments of internalizing symptomatology and a computerized behavioral analog assessment of negative reinforcement–based risk-taking propensity. Results : Results indicated that, overall, female older adolescents were riskier under conditions of negative reinforcement than male older adolescents. In addition, internalizing symptoms significantly moderated the relationship between gender and negative reinforcement–based risk-taking propensity such that the relationship between gender and negative reinforcement–based risk-taking propensity was nonsignificant at high levels of internalizing symptoms, and female gender was significantly positively predictive of heightened negative reinforcement–based risk-taking propensity at low levels of internalizing symptoms. Conclusions : Thus, although female youth overall were riskier, the predictive utility of gender for negative reinforcement–based risk taking may be most relevant at low levels of internalizing symptoms. Results are discussed in terms of implications for future prevention and intervention.